Perencanaan Dan Perancangan Ruang Kreatif Di Badung – Bali ( Badung Creative Space ) - I Made Arista Marta Dinata; Ni Wayan Nurwasih; Gde Bagus Andhika Wicaksana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Creative space is needed in the development of a city where creative space can be a place for social interaction and communication between people, both in groups and individuals or in formal and in-formal terms. Currently, creative spaces are only known as open spaces such as parks or fields, due to the lack of socialization to the public regarding the term Creative Space. This creative space aims to provide facilities that can accommodate creativity for the community and art community as well as umkm to express, be creative and communicate in developing or creating innovative-creative activities. One of them is in Bali, especially Badung Regency which is generally famous for its tourism, where tourism and creative industries complement each other. Badung Regency, which has an advantage in the tourism sector and is the heart of the economy in Bali, is currently pushing the vision to strengthen micro, small and medium enterprises and a community-based creative economy. So it is necessary to provide creative space to accommodate or support these positive activities which can later be used for the training / education process, development and marketing of umkm and communities in Badung. With the provision of creative space facilities, it is hoped that these creative industry players can advance so that they can have a positive impact and can create new jobs for the surrounding community